The essential "Weird Al" Yankovic [compact disc]. - Yankovic, Al, 1959- (Way Moby/Volcano/Legacy : Distributed by Sony Music Entertainment, 2009)
A fabulous collection of some of Weird Al Yankovic's best work, including Yoda; White and Nerdy; Albuquerque; and Another One Rides the Bus.